2020
DOI: 10.1007/s12274-020-3024-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of colloidal polymers from two-patch silica nanoparticles

Abstract: We report the formation of colloidal polymers consisting of disk-like silica nanoparticles (NPs) with polystyrene (PS) chains at the bottom of their two cavities assembled through reduction of the solvent quality for the PS chains and linked by hydrophobic associations. We show that this NPs assembly exhibits a two-stage process involving reaction-controlled polymerization and diffusion-controlled polymerization. Colloidal polymer networks are produced by the incorporation of three-patch NPs, which serve as br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…We found that k = 3.77•10 5 L.mol -1 .s -1 and 1.80•10 5 L.mol -1 .s -1 for the polymerization of 105-nm and 130-nm 2-PSN, respectively. These values are of the same order of magnitude as that found for the chains obtained from 190-nm 2-PSN 25 and for the copolymerization of inorganic nanoparticles. 2 At longer times (t > 5 h), does not vary linearly with time anymore (Figure 4a).…”
Section: Scheme 1 Solvent-induced Assembly Of Divalent Silica Nanopar...supporting
confidence: 81%
See 2 more Smart Citations
“…We found that k = 3.77•10 5 L.mol -1 .s -1 and 1.80•10 5 L.mol -1 .s -1 for the polymerization of 105-nm and 130-nm 2-PSN, respectively. These values are of the same order of magnitude as that found for the chains obtained from 190-nm 2-PSN 25 and for the copolymerization of inorganic nanoparticles. 2 At longer times (t > 5 h), does not vary linearly with time anymore (Figure 4a).…”
Section: Scheme 1 Solvent-induced Assembly Of Divalent Silica Nanopar...supporting
confidence: 81%
“…We previously showed that we assembled 155-nm and 190nm 2-PSN in chains by adding 30 vol.% of salty water into the NPs dispersion in THF, thereby reducing both the electrostatic repulsions between NPs due to negatively charged silanolate groups at their surface and solvent quality for the PS chains (Figure 2e-f and Figure S6). 25 Similar results were obtained when changing the salty water concentration, as shown in Figure 2i. We thus decided to investigate the behavior of the 2-PSN with smaller sizes by adding salty water as bad solvent for the PS chains.…”
Section: Scheme 1 Solvent-induced Assembly Of Divalent Silica Nanopar...supporting
confidence: 78%
See 1 more Smart Citation
“…The formation of the colloidal chains finishes within seconds to minutes, following a step-growth kinetics, according to the direct observation (Figure a,b and Movie S1) and statistical analyses (Figure S2). Initially, the particles assemble by forming directional patch–patch bonds.…”
Section: Resultsmentioning
confidence: 98%
“…By using postassembly ligand photo-cross-linking [26] or by adding monofunctional nanospheres into a suspension of bifunctional gold nanorods [27], it was shown that the average degree of polymerization of the resulting chains could be controlled. The reduction of the solvent quality may be also employed to induce the assembly of silica/polystyrene dumbbells [28] and silica nanoparticles with two PS patches (2-PSN) [29] into multipodlike clusters and colloidal chains, respectively. Here, we report that one-patch silica nanoparticles (1-PSN) with a well-controlled patch-to-particle size ratio (PPSR) assemble into dimers or trimers by following the same strategy.…”
Section: Introductionmentioning
confidence: 99%